Prostate kallikrein markers in diagnosis, risk stratification and prognosis. - Ulmert, D; O'Brien, M; Bjartell, A; Lilja, H (2009)
The kallikrein, prostate-specific antigen (PSA), is one of the world's most frequently used disease biomarkers. After almost two decades of research and clinical experience, the diagnostic and monitoring limitations of PSA are beginning to be understood. Most physicians are aware of PSA's low specificity for cancer among older men with benign prostatic conditions; fewer are aware of recent data, which show that a prior negative biopsy or a prior PSA value below the threshold for biopsy might compromise the predictive accuracy of PSA even further. Furthermore, a subtle increase in serum PSA level during early middle age is strongly correlated with clinically important prostate cancer. We review current and past reports on the prostate kallikreins PSA and hK2 in relation to pathology and epidemiology.